Psychometric properties of the Filipino version of the geriatric depression scale - Melgar, Maria Isabel E. (Danyag :the UPV journal of humanities and social sciences, 2010)
"The present study attempts to translate the Geriatric Depression Scale from its English version to Filipino and evaluate the psychometric qualities of the translated version. The Filipino GDS retained the 30 items and the dichotomous format of the original instrument. The Filipino GDS was administered to a total of 212 elderly participant, with 17 taking the same instrument during the retest phase. The mean age of the participants was 73.3 years. The results showed a strong internal consistency of the Filipino GDS yielding a Cronbach's alpha of 0.87. The test-retest reliability within a span of at most 2 weeks was moderately high (r=0.74, p<01). The odd-even reliability was at r=0.71 (p<0.01) and the split-half reliability was at r=0.74 (p<0.01). The exploratory factor analysis yielded one dominant factor and one minor factor. The 30-item Filipino-translated version of the GDS demonstrated a very good internal consistency with moderate reliability. The local version of the GDS can now be used in clinical settings where screening can be reliably applied to elderly patients whose preferred language is Filipino. Further studies should explore the specificity and sensitivity of the translated scale as well as its convergent validity."